PERSONALITY FACTORS AS PREDICTOR OF WORKPLACE DEVIANT BEHAVIOR AMONG CIVIL SERVANTS - Hastuti, Dwi; Noor, Idris Mohd; Osman, Abdullah; Lubis, Zulkarnain (Jurnal Aplikasi Manajemen, 2017)
The purpose of this study is to investigate empirically the influence of personality traits to workplace deviant behavior among civil servants in Pekanbaru, Indonesia. Using cross-sectional survey method and stratified proportionate random sampling data were conducted to 263 civil servants from various departments and Agencies in Pekanbaru by using questionnaires. The data analyzed using Partial Least Square (PLS). The findings emphasize the importance of taking personality traits into consideration during employee recruitment processes to minimize workplace deviant behavior. This study contributes the important role of employee personality traits in minimizing workplace deviant behavior.The purpose of this study is to investigate empirically the influence of personalitytraits to workplace deviant behavior among civil servants in Pekanbaru, Indonesia.Using cross-sectional survey method and stratified proportionate random sampling datawere conducted to 263 civil servants from various departments and Agencies in Pekanbaruby using questionnaires. The data analyzed using Partial Least Square (PLS). The findingsemphasize the importance of taking personality traits into consideration during employeerecruitment processes to minimize workplace deviant behavior. This study contributes theimportant role of employee personality traits in minimizing workplace deviant behavior.